PENGARUH KUALITAS PRODUK, CITRA MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOBIL JENIS MPV MEREK TOYOTA KIJANG INNOVA DI SEMARANG - Noky Andrianto, Hendra; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2013)
Currently, the development of a fairly rapid rise in population as well as the various work activities everyone lets all activities must be done quickly. So that people can do the work quickly, it means supporting, such as means of transport. One of the means of transportation is a car. Between different types of cars, there is one kind of the most favorite consumers, namely Multi Purpose Vehicle (MPV). When this kind of car MPV having the market share of the highest such as toyota innova, who ranks to 1. Nevertheless, in every year market share Toyota Kijang Innova tending to decline. It shows that also interested consumers to buy brand other than Toyota Kijang Innova. Many factors that could affect the decision this purchase products, like qualities , brand image prices and promotion The population in this research consumers who buy Toyota Innova in Semarang city whose number is unknown. The sample in this study were 96 respondents. Sampling techniques in this research was conducted with the Purposive Sampling technique. Its data type is primary. Method of data collection using the questionnaire. Analysis technique used is multiple regression. The result of analysis shows that product quality, brand image, price, and promotion have positive and sienificant effect on buyine decision. Product quality of Toyota Kijang Innova is relatively grand according to the consumen.